Nilai Fathonah Dalam Pengelolaan Bisnis di Pesantren Mukmin Mandiri Sidoarjo - Fathimatuz Zahroh; Muhammad Nafik HR (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research is aimed to determine the influence of fathonah value actively rolling in every aspect of business management at Pesantren Mukmin Mandiri Sidoarjo. Pesantren Mukmin Mandiri is one of pesantren based on agrobusiness and agro-industry which graduates entrepreneurs every year.This research used the qualitative research method and case study as the strategy. Data collection was done by interviewing and observing the research object directly. The qualitative explanatory was used as the technique of analysis by explaining the results of the interviews and of the direct observations.The results of this research shows that value of fathonah has a good influence in business management at The Pesantren Mukmin Mandiri, it can be seen from the innovation on marketing, production, increased sales, good financial management and proficiency of students in the entrepreneurship.